Utilização de resíduos agroindustriais para a obtenção de moléculas bioativas a partir de microrganismos - Ribeiro, José Evangelista Santos (2018)
In recent years, microalgae and red yeasts have emerged as attractive sources for many bioactive molecules such as carotenoids and fatty acids. However, the use of microorganism cultures to produce commercial products has historically been limited, due to the high costs of these biotechnological processes. The aim of this study was to evaluate the potential of ricotta cheese whey (scotta) and cassava wastewater to be used as low-cost alternative substrates to grow the microalga Chlorella protothecoides and the yeast Rhodotorula glutinis. Furthermore, culture strategies were applied in order to improve the bioactive molecules production. The results suggest that both scotta and cassava wastewater have a great potential to be used as culture mediums to grow the above mentioned microorganisms. C. protothecoides shifted to mixotrophic growth, using the organic carbon source provided when cultured in scotta. Moreover the stress strategy that we applied enhanced carotenogenesis, allowing the cellular accumulation of well quoted carotenoids, namely astaxanthin and lutein/zeaxanthin. The results showed that cassava wastewater can be used as a sole source of nutrients to support R. glutinis growth and metabolites accumulation in its cells. High growth (10.28 g·L-1) as well as high productions of carotenoids (0.98 mg·L-1) and lipids (1.34 g·L-1) were obtained when R. glutinis was cultivated in cassava wastewater as the sole source of nutrients. Moreover, the fatty acids profile from the biomass cultivated in the mediums containing cassava wastewater showed a majority (over 50 %) of unsaturated fatty acids. The agro-industrial by-products studied were efficiently used as carbon sources by the microorganisms and the results obtained for the mediums containing the alternative substrates were even better when compared with the cultivation in synthetic mediums containing similar amounts of organic carbon, which is possibly due to the adequate balance of nutrients in these by-products.